Comparison of the effects of standard vs low‐dose prolonged‐release tacrolimus with or without ACEi/ARB on the histology and function of renal allografts. Issue 6 (1st February 2019) - Cockfield, Sandra M.; Wilson, Sam; Campbell, Patricia M.; Cantarovich, Marcelo; Gangji, Azim; Houde, Isabelle; Jevnikar, Anthony M.; Keough‐Ryan, Tammy M.; Monroy‐Cuadros, Felix‐Mauricio; Nickerson, Peter W.; Pâquet, Michel R.; Ramesh Prasad, G. V.; et al.
Abstract : Targeting the renin‐angiotensin system and optimizing tacrolimus exposure are both postulated to improve outcomes in renal transplant recipients (RTRs) by preventing interstitial fibrosis/tubular atrophy (IF/TA). In this multicenter, prospective, open‐label controlled trial, adult de novo RTRs were randomized in a 2 × 2 design to low‐ vs standard‐dose (LOW vs STD) prolonged‐release tacrolimus and to angiotensin‐converting enzyme inhibitors/angiotensin II receptor 1 blockers (ACEi/ARBs) vs other antihypertensive therapy (OAHT). There were 2 coprimary endpoints: the prevalence of IF/TA at month 6 and at month 24. IF/TA prevalence was similar for LOW vs STD tacrolimus at month 6 (36.8% vs 39.5%; P = .80) and ACEi/ARBs vs OAHT at month 24 (54.8% vs 58.2%; P = .33). IF/TA progression decreased significantly with LOW vs STD tacrolimus at month 24 (mean [SD] change, +0.42 [1.477] vs +1.10 [1.577]; P = .0039). Across the 4 treatment groups, LOW + ACEi/ARB patients exhibited the lowest mean IF/TA change and, compared with LOW + OAHT patients, experienced significantly delayed time to first T cell–mediated rejection. Renal function was stable from month 1 to month 24 in all treatment groups. No unexpected safety findings were detected. Coupled with LOW tacrolimus dosing, ACEi/ARBs appear to reduce IF/TA progression and delay rejection relative to reduced tacrolimus exposure without renin‐angiotensin system blockade. ClinicalTrials.gov identifier: NCT00933231. Abstract : The prevalence and progression of interstitial fibrosis and tubular atrophy over 24 months is reduced in adult de novo kidney transplant recipients who receive low‐dose prolonged release tacrolimus combined with renin‐angiotensin system (RAS) blockers compared to patients who receive low‐dose tacrolimus without RAS blockade or patients who receive standard dose tacrolimus with or without RAS blockade.